Zakat Service Quality, Literacy, and Legal Awareness : Effects on Payment Decisions and Welfare in Jawa Barat - Ahmad Nurkamali; Putri Zafira Ruhliandini; Abdul Hakim; Jelita Syalsabila (Masoem University, 2026)
The potential for zakat in Jawa Barat in 2024 is Rp 26.6 trillion, which is a very large potential. However, the collection of zakat funds managed by zakat administrators under the BAZNAS regulator in the same year was only able to collect zakat, infaq, and sadaqah amounting to 1.9 trillion rupiah, or 7.1 percent of the existing zakat potential. Based on several pieces of literature, factors influencing the low decision-making of zakat payers are the low quality of amilin services, lack of zakatt literacy,and muzakkis legal awareness, which is still not optimal. The decisions of the zakat payer (muzakki) to pay zakat greatly influences the well-being of the recipients (mustahiq). This study aims to determine the influence of amilin service quality, zakat literacy, and legal awareness on muzakki's decision to pay zakat and the welfare of mustahiq. This research method uses a quantitative research type. The research subjects are zakaat payer (muzakki) and zakatrecipient (mustahiq) from the-Muslim community at BAZNAS city and district offices in Jawa Barat. The type of datta used is primary data, with data collection technique using questionaire distributed,to 100 respondentts in six cities in Jawa Barat. The data analysiss techniq uses the SEM-PLS method. The conclusion of this study successfully prove that the service quallity variable of amilin has a significant posittive effects on the variable of muzakkis decision to pay zakat. It was proven that the variables of zakat, literacy and legal awareness have a significant positive influences onthe variable-of muzakki's decision to pay zakat. For the decision variables of the zakat payer (muzakki) paying zakat, it is proven to have a significantly positive effect on the welfare variable. The services qualitty variabel 'amilin' has a positiive but insignificant effect on welfare. Thevariable of zakat literacy was proven to have a neghative and insingificant effects on the variable of welfare. The variable of legal awareness has been proven to have a positive and significants effects on the variable of well-being.